Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian Di Apotek “X” Cilangkap Jakarta Timur Periode April - Mei 2025 - Retno Fitriati; Thassya Nur Utami (PT Bukuloka Literasi Bangsa, 2026)
Service and satisfaction are interrelated aspects. Satisfaction allows all parties to evaluate the quality of services provided, whether they have improved or deteriorated. The purpose of this study was to assess patient satisfaction with pharmaceutical services at Pharmacy